Campus commute mode choice in a college town: An application of the integrated choice and latent variable (ICLV) model. (January 2023) - Kim, Junghwan; Lee, Bumsoo
Highlights: The ICLV model elucidates complex behaviors of campus commute mode choice better than the MNL model. Mode preferences and environmental attitudes are critical determinants of campus commute mode choices. Policy efforts to change commuter attitudes would be as effective as measures that improve actual transportation systems. Abstract: This study examined commute mode choice in a small college town by employing an integrated choice and latent variable (ICLV) model to adequately address the role of attitudinal variables, such as pro-car, pro-bus, and pro-environmental attitudes. The campus commute data (n = 554) came from an individual travel survey of the faculty and staff at the University of Illinois at Urbana-Champaign. The ICLV model provided a richer and more nuanced understanding of the commute mode choice of campus members than a traditional multinomial logit (MNL) model by illustrating how various sociodemographic characteristics influence mode decisions through mode preference and environmental attitudes. Results of a scenario analysis show that policy efforts that aim to shift commuter attitudes toward sustainable modes can be as effective as measures that improve actual transportation systems.